Habitats of the World A Field Guide for Birders, Naturalists, and Ecologists - Campbell, Iain (Princeton University Press, 2021)
The first field guide to all of the world's major land habitats-richly illustrated and packed with essential information to help you get the most out of your outdoor adventuresAccurately identifying and understanding habitats in detail is essential to any birder, naturalist, outdoors enthusiast, or ecologist who wants to get the most out of their experiences in the field. Habitats of the World is the first field guide to the world's major land habitats-189 in all. Using the format of a natural history field guide, this compact, accessible, and comprehensive book features concise identification descriptions and is richly illustrated-including more than 650 color photographs of habitats and their wildlife, 150 distribution maps, 200 diagrams, and 150 silhouettes depicting each habitat alongside a human figure, providing an immediate grasp of its look and scale. Each major habitat has an illustrated "climate box" that allows easy comparisons between habitats. Thirty other illustrated boxes present clear explanations of complex phenomena affecting habitats-from plate tectonics and mountain formation to fire regimes and climate change. Requiring no scientific background, Habitats of the World offers quick and reliable information for anyone who wants a deeper understanding and appreciation of the habitats around them, whether in their own backyard or while travelling anywhere in the world.Covers 189 of the world's major land habitatsProvides all the information you need to quickly and accurately identify and understand habitats anywhere in the worldFeatures concise text, more than 650 color photographs of habitats and their wildlife, an up-to-date distribution map for each habitat, and hundreds of helpful diagrams and illustrations
Description based on online resource; title from PDF title page (publisher's Web site, viewed 27. Okt 2021)
Keywords: NATURE / Ecosystems & Habitats / General; Biogeography; Habitat (Ecology)